Enhancing Brand Identity and Purchase Intention through Digital Marketing Strategy - Lady Lady; Cristina Anggrena; Hepy Hefri Ariyanto; Ronny Firdiansyah Arief (Jurnal MBE Manajemen Bisnis, Equilibrium, 2026)
Addressing the limited empirical evidence on the "zero-to-one" digital transition of micro-scale vendors, this study aims to analyze the implementation of a digital marketing strategy at Uda Denai Juice and its effectiveness in strengthening brand identity and stimulating purchase intention. Using a qualitative case study design and the Stimulus-Organism-Response (SOR) model, data were gathered through semi-structured interviews with the owner and consumers, field observations, and Instagram analytics. Data validity was ensured through technique triangulation. Results indicate that a structured digital system significantly enhanced professional visibility, recording 28,546 views and a reach of 19,592 unique accounts, where 85.7% of engagement originated from non-followers. Qualitative findings reveal that consistent, professional visual content effectively increased consumer trust and brand love, which subsequently drove purchase intention. This study concludes that for micro-enterprises, a well-planned digital strategy is a deterministic factor in building emotional connections. The implications suggest that micro-scale businesses can achieve sustainable resilience by prioritizing a professional digital identity to penetrate new markets independently.